Organizational confidence and its role in improving the performance of staff Field research for a sample of Samaraa University and the Samaraat University staff - et. al., Omar Azeez Abbas , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research is to learn about organizational confidence and its role in improving the performance of staff and to achieve this goal, the researchers have found through the research hypothesis and its change of organizational confidence in its dimensions (confidence in senior management, confidence in the direct president, trust with co-workers). The second change is to improve the performance of staff, where the research sample consisted of 50 staff members at the university and college levels. The most important results were the lack of delegation of authority, participation in decision-making and insufficient attention to work requirements The experience of the management of the system is that the system is not only a function of the system, but also a function of the system. The 2-way